Myogenic differentiation markers in muscle tissue after aerobic training - Rastegar Hoseini; Zahra Hoseini; Ayob Kamangar (Heliyon)
Aerobic training induces a myriad of adaptations in muscle tissue, encompassing alterations in muscle fiber type composition, hypertrophy, and metabolic capacity. Understanding the potential role of myogenic differentiation markers (MDFs), such as Pax7, MyoD, Myogenin, and myosin heavy chain (MHC) isoforms, in mediating these adaptations is of paramount importance. The review delves into the intricate molecular mechanisms underlying the regulation of MDFs following aerobic training, elucidating the role of key signaling pathways including the MAPK/ERK, PI3K/Akt, and AMPK pathways, among others. These pathways play pivotal roles in orchestrating the expression and activity of MDFs, ultimately influencing muscle adaptation and regeneration. The comprehension of MDFs in the context of aerobic training is far-reaching, offering the potential for targeted interventions to optimize muscle adaptation and regeneration. This review identifies the need for further research to unveil the precise molecular mechanisms of the activation and interaction of myogenic differentiation markers with other signaling pathways, as well as to explore their potential as therapeutic targets for muscle-related conditions. This review article also provides a thorough analysis of MDFs in muscle tissue after aerobic training, highlighting their potential clinical implications and outlining future research directions in this area.